Taxation and Government Revenue Mobilization: A Study of the Delta State Board of Internal Revenue Services - Ojaduvba Jame Augoye (Journal of Social Science and Humanities, 2026)
This study, titled "Evaluation of Taxation as a Source of Government Revenue in Delta State Board of Internal Revenue Services," examines the role and effectiveness of taxation in supporting public revenue generation and development in Delta State, Nigeria. Using an ex post facto research design, the study addresses three primary research questions and hypotheses to understand the impact of taxation on health, education, and economic growth within the state. The population for this study consisted of 120 employees from the Delta State Board of Internal Revenue Services. Data were collected through a structured questionnaire, and responses were analyzed using mean scores to assess research questions, with a mean criterion of 2.50 as the benchmark for acceptance. Additionally, chi-square analysis was employed to test the hypotheses. The findings revealed significant positive relationships between internally generated revenue and government expenditure on health and education, underscoring the importance of efficient tax collection in funding essential public services. Results also indicated that tax evasion and avoidance negatively impact revenue generation, reducing the funds available for development projects. Furthermore, the study found that taxation contributes to economic growth, evidenced by its role in enhancing Delta State’s Gross Domestic Product (GDP). Based on these results, the study recommends that the Delta State Board of Internal Revenue Services strengthen tax collection mechanisms, improve public awareness on tax compliance, and allocate revenue strategically to critical sectors such as health and education